Avaliação dos níveis de IL-6 e IL-33 em pacientes com síndrome mielodisplásica - Falcão, Luciana de Brito (2020)
Myelodysplastic syndromes (MDS) are a heterogeneous and complex group of hematopoietic clonal diseases usually characterized by the presence of peripheral cytopenias, dysplasias, genetic/epigenetic changes, medullary microenvironment changes, and inflammation. Several studies have linked chronic inflammation to the development of cancer. Inflammation potentially induces tumor progression in several types of neoplasms, mainly in solid tumors, however, there are few studies that address the role of inflammation in the onset and progression of hematological neoplasms. The objective of this work is to investigate the cytokyne profile (IL-6 and IL-33) and correlate then to the clinic of patients with MDS in order to better understand the inflammation and their role in MDS. The study included 101 patients with confirmed MDS diagnosis from Walter Cantídio University Hospital and 59 controls (non-MDS patients aged 55 to 92 years). The cytokines (IL-6 and IL-33) were measured in the plasma of patients using Enzyme-Linked Immunosorbent Assay (ELISA) method, by means of the DuoSet ELISA (R&D Systems) kits. All statistical analyzes were performed using the SPSS Statistics 21 software and using the non-parametric Mann–Whitney end Kruskal-Wallis tests. And the GraphPad Prism 6 software was used to plot the results. The characterization of the studied population revealed a predominance of female patients, of primary MDS, of the initial stage of the disease, very low and low-risk MDS. The analysis of the concentration of cytokines IL6 and IL-33 demonstrated that the amount of IL-6 is greater in patients with MDS than in the control group and that for IL-33 the opposite occurs. Such analysis has also showed increased IL-6 in patients with intermediate prognosis compared to very favorable prognosis; decreased IL-33 in patients with complex karyotype and in the advanced disease stages. Due to scarce studies of the role of IL-33 in MDS, its potential therapeutic use as an immunomodulatory agent should be considered with caution. Fully comprehension of the role of inflammatory cytokines in each stage of the disease can potentially provide new diagnosis and prognosis markers and new therapeutic targets.